Export Spillovers from Global Shocks for the Middle East and Central Asia - Behar, Alberto (IMF Working Papers; Working Paper, 2014)
This paper quantifies the effect of realized and potential global growth disappointments on export volumes from the Middle East, North Africa, the Caucasus, and Central Asia. Estimates of export elasticities with respect to trading partner GDP indicate non-oil export volumes are relatively responsive while service exports are less responsive. Downward revisions to global GDP growth for 2011-14 have impeded export performance, and the possibility of disappointing GDP growth in Europe and emerging markets presents further downside risks for exports. The Maghreb countries are particularly sensitive to developments in Europe, while CCA countries are more susceptible to growth in the BRICS.